Training of Trainers on Enhancing Forecasting Capacities and Crop Capability Prediction Model/Tool, Ezulwini, Eswatini - Garanganga, Bradwell; Nyakutambwa, Trymore; Magagula, Futhi; Amha, Yosef; Ambaw, Geberemedihin; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The negative impact of hydro-meteorological hazards on the agricultural sector oftentimes leads to food insecurity, especially in Sub-Saharan Africa (SSA). It is, therefore, incumbent upon policymakers to formulate appropriate strategies to minimize the effects of hydro-meteorological hazards on communities and economies. Increased availability of timely and tailored climate-related Knowledge, information, and products supports decision-makers in reducing climate-related losses and enhancing benefits. In this regard, regional partners (AICCRA, ACPC, UNECA, WMO, CCARDESA) commissioned Digitron to conduct a series of Training of Trainers workshops and to refine a Crop Capability Prediction Tool to maximize agricultural productivity while limiting the consequences of hydro-meteorological risks on the food system. This tool can assist policymakers and user communities in deciding on the most up-to-date crop capability based on seasonal climate forecast (SCF). However, roving training of trainers (ToT) workshops are required for agricultural yield prediction users, SCF providers, researchers, and academics in the Southern Africa Development Community (SADC) region to operationalize and bring maximum impact. In this regard, the first of such ToT workshops was held in Harare, Zimbabwe, in July 2022. The second was held in Maputo, Mozambique. The third ToT workshop was held in Livingstone, Zambia, from 19 to 22 September 2023, and in Lilongwe, Malawi, from 9 to 13 December 2024. The current national workshop was held in Ezulwini, Eswatini, from 12 to 16 May 2025 and attended by 21 technical experts (14 men and 7 women) from the University of Eswatini, the Ministry of Agriculture, the Eswatini Meteorological Services (EMS), and other relevant departments. This ToT workshop covered a wide range of topics, including providing a conceptual framework for the Climate Agriculture Modelling and Decision Tool (CAMDT) - Decision Support System for Agrotechnology Transfer (DSSAT) platform; the importance of SCF; a ‘Hands-on’ Exercise in data management (quality control and missing values, as well as a specific template/format); data acquisition; model descriptions (assumptions and uncertainties); and model analysis (simulation and validation). Participants' feedback indicated that running the model and interpreting its outputs were easy and acknowledged the feasibility of the tool for future applications. However, despite the availability of a user manual, participants preferred a more straightforward programme-assisted method so that individuals with less computer knowledge could run the model for immediate use and application. They also thought the training was extremely relevant and valuable to the user communities. From the hands-on exercise, participants emphasized that the proper use of the SFC-driven crop capability prediction model and its timely deployment will result in large savings, considering agriculture's vital role in the SADC area. Participants also recommended improving the model by including local circumstances and cultivars for its comprehensive applicability in Eswatini and beyond. Digitron showed some improvements in the Tool to improve usability by enabling users to input crop coefficients and soil profiles. Furthermore, stakeholders demonstrated the joint post-processing of tool outputs through a formalized framework for simple interpretation. However, there was need for resources to finalize these joint products for customization and, therefore, greater usability. Eswatini requested support from Digitron to customize the Tool with the requisite capacity building for greater usability. The participants recommended that, for this capacity-building programme to be successful and have a lasting impact, the pertinent national and regional organizations, projects, and governments in the area must be fully supported. More resources are also required to guarantee that developers continue to engage in model improvement and skill transfer within SADC and beyond.